Association of Single-Nucleotide Polymorphisms of MAFB Gene with Nonsyndromic Cleft Lip with or without Cleft Palate in Kinh Vietnamese Patients - Phan, Hoanh Duy Ba; Phuong, Lam Hoai; Vu, Hoang Anh (Indian Journal of Plastic Surgery, 2022)
Background Cleft lip with or without palate (CL/P) is the most common orofacial birth defect. Single-nucleotide polymorphisms (SNPs) in MAFB gene (V-Maf avian musculoaponeurotic fibrosarcoma oncogene homolog B) were identified as susceptible to this defect in a genome-wide association study. To further evaluate its role in this birth defect, we conducted this study with the aim of identifying allele frequencies, genotype frequencies, and association of SNPs rs13041247, rs6065259, and rs6072081 of MAFB gene with nonsyndromic cleft lip/palate (NCL/P) in Kinh Vietnamese patients.Methods We performed case–control study involved 79 patients with NCL/P and 77 healthy controls. DNAs were extracted from participants' saliva and tetra-amplification refractory mutation system polymerase chain reaction (tetra-ARMS PCR) was used for genotyping SNPs.Results SNPs of MAFB gene were genotyped using the Tetra-ARMS PCR method. We found that genotype CT of rs13041247 was associated with an increased risk of NCL/P in Kinh Vietnamese (odds ratioTCTT [ORTC/TT] = 1.63, 95% confidence interval [CI] = 0.83–3.19, p = 0.17). The G allele genotypes of SNP rs6072081 increase high risk for the malformation, statistically significant result (ORGG/AA = 7.06, 95% CI = 2.13–23.42, p < 0.001). There is no clear association between rs6065259 and CL/P (ORAA/GG = 0.75, 95% CI = 0.22–2.50, p = 0.32; ORAG/GG = 1.53, 95% CI = 0.79–2.97, p = 0.32). When the patients were divided into the phenotypic subgroups, there was a similar significant trend between the patients and controls for all SNPs.Conclusions Our study provides further evidence of role of MAFB gene variations with NCL/P defect in Kinh Vietnamese.
Keywords: cleft lip; MAFB; SNPs; Vietnamese